2014
DOI: 10.1111/ijfs.12597
|View full text |Cite
|
Sign up to set email alerts
|

Changes during ripening in chemical composition, proteolysis, volatile composition and texture in Kashar cheese made using raw bovine, ovine or caprine milk

Abstract: Summary Kashar cheeses were manufactured from pure ovine (OV), bovine (BV) and caprine (CP) milk, and the chemical composition, cheese yield, proteolysis, hardness, meltability and volatile composition were studied during 90 days. Gross chemical composition, cheese yield and level of proteolysis were higher in OV cheeses than those of BV or CP cheeses. Glu, Val, Leu, Phe and Lys were the most abundant free amino acids (FAA) in the samples, and the concentrations of individual FAA were at the highest levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
(61 reference statements)
9
15
0
Order By: Relevance
“…Similar situations have been reported in other countries (Aminifar et al, 2013). Depending on milk sources and processing conditions, quality properties of the cheese show a great variation (Oktar et al, 1996;Hayaloğlu et al, 2002;Temizkan et al, 2014).…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…Similar situations have been reported in other countries (Aminifar et al, 2013). Depending on milk sources and processing conditions, quality properties of the cheese show a great variation (Oktar et al, 1996;Hayaloğlu et al, 2002;Temizkan et al, 2014).…”
Section: Introductionsupporting
confidence: 65%
“…Increase of WSN content was significantly higher in the ovine and caprine cheeses than the bovine cheeses at 120 and 180 days of ripening period (p<0.01) (Figure 1). Temizkan et al (2014) found caprine cheeses had lower levels of soluble nitrogenous matters than those of bovine or ovine cheeses during ripening. Aminifar et al (2013) reported higher WSN values in cheese from ovine milk compared with bovine milk cheese.…”
Section: Biochemical Changesmentioning
confidence: 79%
See 2 more Smart Citations
“…The results were expressed as peak area/100 000; b Temizkan et al . . Results were expressed as μg/100 g cheese.…”
Section: Resultsmentioning
confidence: 99%